Perempuan dalam Nafkah Rumahtangga (Kajian di Wilayah Pertanian Lahan Kering Kabupaten Wonogiri) - Saraswati, Yudhistira (Program Studi Agribisnis, Fakultas Pertanian, Universitas Singaperbangsa Karawang, 2023)
The involvement of women in household income makes a major contribution to household sustainability. In the other side, women in livelihood activities are considered only as supporters. This study aims to identify the role of women in household income. The approach was used descriptive qualitative. The location is in Wonogiri Regency where is dry land farming area. The results showed that women in farming households relied on natural and human capital, meanwhile women in non-agricultural households maximized physical and financial capital to carry out livelihood strategies. The role of women in household income as the main source of household structure, role in diversification livelihood, household business workers, remittance, and role in household resilience. Women in non-agricultural households play all of these roles, but women in farming households only support the main source of livelihood. That is because the majority of women in farming generate income in kind so that it is felt that they do not contribute much to the household income structure.